3D hydrogel environment rejuvenates aged pericytes for skeletal muscle tissue engineering - Fuoco, Claudia; Sangalli, Elena; Vono, Rosa; Testa, Stefano; Sacchetti, Benedetto; Latronico, Michael V. G.; Bernardini, Sergio; Madeddu, Paolo; Cesareni, Gianni; Seliktar, Dror; Rizzi, Roberto; Bearzi, Claudia; et al. (Frontiers in Physiology, 2014)
Skeletal muscle tissue engineering is a promising approach for the treatment of muscular disorders. However, the complex organization of muscle, combined with the difficulty in finding an appropriate source of regenerative cells and in providing an adequate blood supply to the engineered tissue, makes this a hard task to face. In the present work, we describe an innovative approach to rejuvenate adult skeletal muscle-derived pericytes (MP) based on the use of a PEG-based hydrogel scaffold. MP were isolated from young (piglet) and adult (boar) pigs to assess whether aging affects tissue regeneration efficiency. In vitro, MP from boars had similar morphology and colony forming capacity to piglet MP, but an impaired ability to form myotubes and capillary-like structures. However, the use of a PEG-based hydrogel to support adult MP significantly improved their myogenic differentiation and angiogenic potentials in vitro and in vivo. Thus, PEG-based hydrogel scaffolds may provide a progenitor cell “niche” that promotes skeletal muscle regeneration and blood vessel growth, and together with pericytes may be developed for use in regenerative applications.